Pengaruh Ukuran PerusahaanTerhadap Kinerja Intelectual Capital dengan Stuktur Kepemilikan sebagai Variabel Moderating Di Bursa Efek Indonesia - Haifah Haifah; Wiwik Fitria Ningsih; Angga Ade Permana (STIE Mandala Jember, 2021)
This study aims to test empirically regarding the effect of company size on the intellectual capital performance of banking companies listed on the Indonesia Stock Exchange. This study uses Classical Assumption Analysis, VA, VACA, VAHU and STVA to measure the Performance of Intellectual Capital also using Multiple Regression analysis, Determination Test , F test, t test also Moderated Regression Analysis (MRA) To test empirically the effect of institutional ownership structure on the relationship between company size and intellectual capital performance of banking companies listed on the Indonesia Stock Exchange. The population of this study is 43 listed banking companies. in the Indonesia Stock Exchange in 2014-2018 where the research sample was taken using the simple random sampling method of 11 samples. The results show that the size of the company does not have an influence on the intellectual capital performance of commercial bank companies listed on the Indonesian Stock Exchange for the period 2014-2018. And that the institutional ownership structure has no effect on the relationship between company size and the intellectual capital performance of commercial bank companies listed on the Indonesia Stock Exchange for the period 2014-2018. Keywords: Company Size; Intellectual Capital Performance; Institutional Ownership Structure